Peran Kompetensi Pedagogik Guru: Perencanaan, Implementasi, dan Evaluasi Pembelajaran di Taman Kanak-Kanak - Nurul Layly, Anis; Dian Pertiwi, Adharina; Aprilia Pangestu Putri, Ayu (Institut Agama Islam Negeri Madura, 2024)
The purpose of this study is to find out how the pedagogic competence of teachers in understanding student characteristics, designing and implementing learning and learning evaluation at Al-Kautsar Bontang Kindergarten. This research was conducted through a qualitative approach, which is a type of narrative research. This study collects data through observation, interviews, and documentation. Primary and secondary data are included in the dataset used for the study, and the analysis is carried out through data reduction, data presentation, and conclusion drawn. The results of this study show that in understanding the characteristics of students, teachers conduct diagnostic assessments, interviews and observations. In learning planning, teachers design starting with annual, semester, weekly and daily programs. The implementation of learning activities begins from the opening, core and closing activities. Teacher evaluations are carried out weekly or monthly for the results of pedagogic competency performance in learning and also schools bring in resource persons to improve teachers' pedagogic competence.